20+x=-13

Simple and best practice solution for 20+x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20+x=-13 equation:


Simplifying
20 + x = -13

Solving
20 + x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + x = -13 + -20

Combine like terms: 20 + -20 = 0
0 + x = -13 + -20
x = -13 + -20

Combine like terms: -13 + -20 = -33
x = -33

Simplifying
x = -33

See similar equations:

| 2-T/3=T/6 | | 5k+2=3 | | 3(5n-1)^1/3-2 | | p/8-1=3 | | 5/8=x-1/x-4 | | w/5-2=4 | | 10+x+9=21 | | X+x+.87+x+.87+.41=10.70 | | (6t^2-12t)/t-2 | | -4(x-10)=-8(x-5) | | 4(x-3)=6-(x+4)+1 | | (x-5)=7x-27 | | 12y-3y-6=9 | | 8/9h=48 | | X/3-1=-5 | | 2f^2+8h+3=3 | | a/6-1=4 | | 9m-2=-26+5m | | 5t-16=-44+9t | | -10+2x=-2 | | 22d/2=14 | | 21x^2+5x-9=0 | | h=-16t^2+96t+880 | | Logs=3.1 | | 5x/4=16 | | 7m+4=24.28 | | (x+10)-(3x+12)=7x+12(11.4) | | z-18/-2=7 | | H=16t^2-16t+60 | | 3(x-2)=2-(x+3)+4 | | k+4=7k-4 | | 2x^2=13-6x |

Equations solver categories